Determination of Dielectric Constants through Capacitor Measurement Using Variations in Thickness, Area, Materials, and Density - Rohman, Syifa Nailufar; Khairina, Jasmine; Julaeha, Juju; Khotimah, Siti Nurul (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
In this study, the researchers focused on testing experimental media from Yeti Rusmiati to measure the dielectric constant of capacitors, with variations in thickness, surface area, material, and density. The experimental results show that the thicker the dielectric material, the smaller the capacitance value. This applies to all materials tested, namely mica, silicon, and duplex paper, with errors from largest to smallest being 24.97% duplex, 7.27% mica, and 0% silicon. Measuring the capacitance of parallel plate capacitors with variations in plate area from GRC gypsum, silicon rubber, and mica, it was found that the error from largest to smallest is mica 11.56%. In comparison, silicon rubber and GRC gypsum have an error of 0%. Measurement of capacitance by varying the dielectric material shows that the capacitance value of the capacitor is proportional to the dielectric constant of the material. Among all the 12 materials tested, the highest dielectric constant is banana leaves with a value of ? = 12.6 and the smallest flannel with a value of ? = 1.02. In contrast, the variation in density shows that the greater the density, the greater the dielectric constant, from the largest to the smallest, the variation in density of leaves steamed with fire, fresh leaves 1 x 24 hours, and dry leaves heated with the sun, respectively 67.51;22.96; 16.57. It can be concluded that Yeti Rusmiati's media can be used in measuring dielectric constant with variations in thickness, area, density, and dielectric material in learning capacitors.